σ- and π-Hole Interactions (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book describes unconventional noncovalent interactions and analyzes their importance for crystal growth in organic and hybrid organic–inorganic systems. Several examples illustrate how the combination of theory and experiment allows rationalizing the strength and directionality of noncovalent interactions. This book elegantly describes the results of a survey of X-ray structures of main group element compounds (M = Sn, Pb As, Sb, Bi, and Te) exhibiting intermolecular M•••Se noncovalent interactions in one of its chapters. Moreover, it provides a consistent description of noncovalent interactions, covering most groups of the periodic table. The interactions are described and discussed using their trivial names. That is, a comprehensive and accurate description is provided for alkali, alkaline earth, regium, spodium, triel, tetrel, pnictogen, chalcogen, halogen, and aerogen bonding interactions. No other book is available covering such an extensive number of interactions and examples where these interactions are relevant. relevant.